GENETIC VARIABILITY STUDIES IN CHILLI ( ARIABILITY STUDIES IN CHILLI (Capsicum annuum Capsicum annuum Capsicum annuum L.) IN MID HILLY REGIONS OF UTTARAKHAND - SILARU RAGHUVEER , SATISH CHANDRA PANT, RAJENDRA SINGH CHAUHAN, PANKAJ BAHUGUNA, (The Bioscan, 2018)
The present investigation was carried out during Kharif 2016 at College of Horticulture, Bharsar with 19 genotypes of chilli (Capsicum annuum L.) in a Randomized Block Design with 3 replications to estimate the genetic variability, heritability and genetic advance for 24 traits. Analysis of variance revealed significant differences among the genotypes for all the traits studied indicating the presence of sufficient variability in the studied material. The GCV was higher than PCV and the difference between PCV and GCV was narrow for most of the characters revealing little influence of the environment in the expression of these traits. High magnitude of PCV and GCV were observed for all the traits studied except plant stem girth (9.74, 12.18), days to first flowering (5.10, 5.84), days to 50% flowering (3.2, 4.30) and capsaicin content (3.20, 4.18). High heritability coupled with high genetic advance as per cent of mean was observed for all the characters except plant height(34.64), plant stem girth (63.87), days to first flowering (76.24), days to 50% flowering (55.23) and capsaicin content (58.69) indicating the predominance of additive gene action making the simple selection more effective